2016
DOI: 10.1653/024.099.0343
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of an Introduced Weed Biological Control Agent,Megamelus scutellaris(Hemiptera: Delphacidae), by a Native Parasitoid

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The no-insect control also varied from the multiple release of adults treatment specifically with fewer adult M. scutellaris found (p = 0.04), fewer mites found (p = 0.01), and fewer K. ema found (p = 0.04), and from the single release of an infested plant treatment with fewer N. eichhorniae adults (p = 0.003) and mites found (p = 0.01). Minteer et al (2016) noted that parasitism occurred more often when M. scutellaris and E. crassipes were at artificially high densities compared to field sites. As this experiment was conducted at the same facility as the rearing tanks in Minteer's study, it is likely that parasitism played some part in the population dynamics of M. scutellaris.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The no-insect control also varied from the multiple release of adults treatment specifically with fewer adult M. scutellaris found (p = 0.04), fewer mites found (p = 0.01), and fewer K. ema found (p = 0.04), and from the single release of an infested plant treatment with fewer N. eichhorniae adults (p = 0.003) and mites found (p = 0.01). Minteer et al (2016) noted that parasitism occurred more often when M. scutellaris and E. crassipes were at artificially high densities compared to field sites. As this experiment was conducted at the same facility as the rearing tanks in Minteer's study, it is likely that parasitism played some part in the population dynamics of M. scutellaris.…”
Section: Discussionmentioning
confidence: 95%
“…Five months following the last plant or insect releases (JD 026 in 2015 and JD 017 in 2016), treatments were sampled for M. scutellaris and then evaluated destructively by sampling five haphazardly selected plants per mesocosm to measure N. eichhorniae densities, insect damage, and plant biomass. Other insects were also counted from this sample, including Elophila (Synclita) obliteralis Walker (Lepidoptera: Crambidae), a native moth commonly found on E. crassipes in Florida (Habeck et al, 1986), and Kalopolynema ema Schauff & Grissell (Hymenoptera: Mymaridae), a native egg parasitoid that utilizes M. scutellaris (Minteer et al, 2016), as well as two mite species (the introduced Orthogalumna terebrantis Wallwork [Acari: Galumnidae] and the native Tetranychus tumidus Banks [Arachanida: Tetranychidae]; Center, 1987). Remaining plant material was bulked and placed in Berlese funnels for one week, after which collection vials were examined and the numbers of arthropods tallied.…”
Section: Release Methodsmentioning
confidence: 99%
“…Three biological control species namely Neochetina eichhorniae Warner (Coleoptera: Curculionidae), Neochetina bruchi Hustache (Coleoptera: Curculionidae) and Niphograpta albiguttalis (Warren) (Lepidoptera: Crambidae) (Center et al, 2002) were introduced previously but are vulnerable to herbicides which, by killing the plants, eliminates large portions of the internally feeding immature stages of their populations. Megamelus scutellaris was developed specifically to deal with the wide-scale use of herbicides because nymphs and adults feed externally and can move readily from sprayed to unsprayed plants (Tipping, Center, Sosa, & Dray, 2011 (Minteer et al, 2016). Pontederia crassipes readily invades and dominates communities with floating leaves like N. advena to the extent where N. advena, and presumably its herbivores, are often locally extirpated (Center et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…External feeding by M. scutellaris likely promotes more novel interactions by increasing their vulnerability to generalist predators and stenophagous parasitoids like Kalopolynema ema (Schauff and Grissell) (Hymenoptera: Mymaridae) that commonly attacks the eggs of hemipteran species including the native congener M. davisi Van Duzee (Hemiptera: Delphacidae), a specialist herbivore on the native aquatic plant Nuphar advena (Aiton) W. T. Aiton (Nymphaeaceae) (Minteer et al, 2016). Pontederia crassipes readily invades and dominates communities with floating leaves like N. advena to the extent where N. advena , and presumably its herbivores, are often locally extirpated (Center et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Although native parasitoids are known to utilise M. scutellaris in its extant range, overall parasitism is relatively low (Minteer et al 2016). Tipping et al (2020) found no evidence of apparent competition between M. scutellaris and M. davisi, a native planthopper with the shared native parasitoid Kalopolynema ema (Schauff and Grissell) (Hymenoptera: Mymaridae) in Florida.…”
Section: Introductionmentioning
confidence: 99%